2014
DOI: 10.1007/s00737-014-0450-7
|View full text |Cite
|
Sign up to set email alerts
|

Time trends of antidepressant drug prescriptions in men versus women in a geographically defined US population

Abstract: Purpose To study time trends of antidepressant drug (AD) prescriptions in a geographically defined US population between 2005 and 2011 for men and women separately. Methods Using the Rochester Epidemiology Project medical records-linkage system, we identified all Olmsted County, MN residents who received AD outpatient prescriptions between 2005 and 2011 (seven years). We calculated the annual age-and sex-specific prevalence over seven years, and used generalized estimating equation models to test for time tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 31 publications
2
15
0
1
Order By: Relevance
“…The prevalence and incidence of AD prescriptions was consistently higher amongst females than males. Although, as found in some previous studies [ 25 , 26 ] there was a decrease in the ratio of female to male prescribing over time, indicating that AD prescribing has increased more in males. This could suggest there has been an increase in help-seeking behaviour in males, an increase in depression, or an increase in the number of males prescribed an AD for other indications.…”
Section: Discussionsupporting
confidence: 66%
“…The prevalence and incidence of AD prescriptions was consistently higher amongst females than males. Although, as found in some previous studies [ 25 , 26 ] there was a decrease in the ratio of female to male prescribing over time, indicating that AD prescribing has increased more in males. This could suggest there has been an increase in help-seeking behaviour in males, an increase in depression, or an increase in the number of males prescribed an AD for other indications.…”
Section: Discussionsupporting
confidence: 66%
“…In this study, we found that approximately 1.6 times more antidepressant prescriptions were prescribed to women than to men. This is not surprising, given that the prevalence and incidence of depression, as well as other psychiatric disorders such as anxiety and bipolar disorder, have previously been found to be higher for women than for men ( 20 , 24 26 ). There was no difference in the sex ratio for antidepressant visits across the study years, which indicates that the relative distribution of the burden of depression and related conditions between men and women has not changed.…”
Section: Discussionmentioning
confidence: 85%
“…Other studies have examined trends in use of treatments for specific conditions (such as depression and anxiety disorders) or specific types of treatments (such as antidepressants and psychotherapy).…”
Section: United Statesmentioning
confidence: 99%